The Influence of Product Innovation, Green Products, And Promotion on Buying Intention for Electric Cars - Gosari, Steven Frendrik; Pranoto, Yeremia Geraldi; Kamasi, Jason Raphael; Muchtar, Muchtar (Jurnal Economic Resource, 2025)
This research aims to analyze the influence of product innovation, green products, and promotion on consumer purchase decisions, with a particular emphasis on the case of electric cars. This research employs a quantitative approach, collecting data through questionnaires that involve 102 respondents. Data analysis was carried out using SmartPLS 4 software, which is based on Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis process involves a measurement model to connect indicators with the measured constructs, as well as a structural model to test relationships between constructs. The research results show that green products and promotions have a significant positive influence on purchase decisions. Product innovation does not show a significant influence. This has implications for marketing strategies, particularly in increasing the attractiveness of green products and promotions to encourage the purchase of electric cars. This research also focuses on three main variables and a quantitative approach that delves deeper into consumers' subjective perceptions. Therefore, it is recommended that further research be conducted by incorporating additional variables, such as brand loyalty and price, and employing a mixed-methods approach for more comprehensive insights.